Rural electricity supply and its improvement : a case of Thakhek district, LAO P.D.R. - Boun-oum Syvanpheng; Yu, Chin Yi; Surapong Chiraratananon; Malik, Arif Saeed; SIDA (Bangkok : Asian Institute of Technology, 1997)
This paper has been discussed the power sector in Laos including an overview, development of power sector, target and option of extension electricity supply to rural area, where have access to be electrified only 2% of rural households representing 85% of the total population . This study has been analyzed the power loss and voltage drop in existing primary distribution system in Thakhek district by different approach. Suggested way to reduce loss and voltage drop in primary feeders as an overall system and computed it economic evaluation. This paper also has been compared line losses using two calculation method, one is basic method and another is equivalent method. Finally, the general recommendation to reduce power loss as a saving energy in Thakhek distribution system in order to get benefits for utility as EDL and domestic consumers.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Rural electrification -- Laos